Pengolahan Kotoran Ternak Menjadi Pupuk Organik Dalam Upaya Meningkatkan Pendapatan Peternak Pada Kelompok Tani-Ternak “Beriuk Taker” Di Desa Dasan Cermen Kecamatan Sandubaya Kota Mataram - Soekardono Soekardono; M. Yasin; Anwar Fachry; Moh. Taqiuddin; Maya Nachida (Jurnal Gema Ngabdi, 2021)
City of Mataram City is the center of government and economic activity. Urban-Village of DasanCermen, district of Sandubaya, has been selected as site of community service with consideration that there are several livestock-farmers group, namely: the cattle-farmers group, the Buras Chicken-Farmer Group, the Duck-Farmers Group, and the Fish- Farmers Group. The existence of these livestock-farmer groupshave been used as an educational tourism-site by the Urban-Village Government. The cattle-farmer group of “Beriuk Taker” is located close to the urban-village office and residential areas so that accumulated-manure disturbs environmental health. Therefore, the aim of this community service is to find solution problem of accumulated-livestock manure by processing it into organic fertilizer. In addition, this service also provides knowledge and skills about group-based business management to group committee.The methods have been used in this activity are extension service on implementation of cattle-business technology, training on processing organic fertilizers, and focus group discussions (FGD) on cattle-group management. The service results showed: (1) positively response of beneficiary group to the community service; (2) cattle-farmers capable and willing to apply technology about feed, cattleshed, and marketing;(3) cattle-farmers are skilled in processing of organic fertilizer by mutually work in every Sunday after zuhr prayer. The processing of organic fertilizer can produce 1 – 1.5 tons in 3 weeks. The temporary marketing is directed to ornamental-plant entrepreneurs around in the city of Mataram. It is hoped that the proceeds from the sale of fertilizers can be used to pay land rent to the local mosque management. With the support of the village government, the "Beriuk Taker" cattle farmer group can be used as a location for livestock education. They planned that the income from sale of organic fertilizerwould be used to pay land-rent to the local mosque committee.With the support of the urban-village government, the cattle-farmers group of "Beriuk Taker" can be used as site for livestock’educational-tourism.